2012
DOI: 10.1371/journal.pone.0044139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cadmium Exposure during Pregnancy on Hepatic Glucocorticoid Receptor Methylation and Expression in Rat Fetus

Abstract: Adverse fetal environment due to maternal undernutrition or exposure to environmental chemicals alters glucocorticoid (GC) metabolism increasing the risk of metabolic disorders in adulthood. In this study, we investigated the effects of maternal exposure to cadmium (Cd, 50 ppm) during pregnancy in the methylation of fetal hepatic glucocorticoid receptor promoter (GR) and the correlation with its expression and that of the DNA methyltransferases (DNMT1a and 3a). We also studied the expression of liver phosphoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 63 publications
(77 reference statements)
1
26
0
Order By: Relevance
“…The silencing of p16 INK4A and caspase8 by Cd in melanoma cells that we have shown is of particular importance in the light of several considerations. As constitutional epimutations of CDKN2A (p16 INK4A and p14 ARF ) genes in melanoma families play a negligible role (Castillo et al, 2012) and no association has been found between the risk of cutaneous malignant melanoma and peripheral blood mononuclear cell methylation levels of p16 INK4A (Zhang et al, 2009), it is apparent the crucial role of the environment in inducing epigenetic changes in a key gene in melanoma development we have evidenced. This is even more relevant in light of the contribution of p16 INK4A in uveal melanoma (Hearle et al, 2003;Buecher et al, 2010) and the correlation of p16 INK4A promoter methylation with increased melanoma thickness (Kostaki et al, 2014), and more, of the association between loss of CDKN2A expression and adverse prognostic markers of melanoma (Young et al, 2014;Lade-Keller et al, 2014;Chang and Cassarino, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…The silencing of p16 INK4A and caspase8 by Cd in melanoma cells that we have shown is of particular importance in the light of several considerations. As constitutional epimutations of CDKN2A (p16 INK4A and p14 ARF ) genes in melanoma families play a negligible role (Castillo et al, 2012) and no association has been found between the risk of cutaneous malignant melanoma and peripheral blood mononuclear cell methylation levels of p16 INK4A (Zhang et al, 2009), it is apparent the crucial role of the environment in inducing epigenetic changes in a key gene in melanoma development we have evidenced. This is even more relevant in light of the contribution of p16 INK4A in uveal melanoma (Hearle et al, 2003;Buecher et al, 2010) and the correlation of p16 INK4A promoter methylation with increased melanoma thickness (Kostaki et al, 2014), and more, of the association between loss of CDKN2A expression and adverse prognostic markers of melanoma (Young et al, 2014;Lade-Keller et al, 2014;Chang and Cassarino, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, gestational exposure to environmental endocrine disruptors, especially non-genotoxic chemicals, can induce functional disorders in offspring through the alteration of genome methylation. Several reports have supported this hypothesis (Castillo et al, 2012;Manikkam et al, 2012a;Sanders et al, 2014).…”
Section: Introductionmentioning
confidence: 80%
“…Cadmium is a partial transplacental toxic metal, accumulating in the placenta, and has been implicated as a potential cause of adverse birth outcomes [65]. Specifically, in a rat model, prenatal exposure to cadmium altered methylation of the hepatic glucocorticoid receptor [17], which may correlate with human data demonstrating an altered glucocorticoid response in human placental trophoblasts following cadmium exposure [66]. A lack of epigenetic data on the role of cadmium in glucocorticoid-related stress responses in utero represents a major gap in current understanding of the molecular mechanisms of intrauterine cadmium exposure.…”
Section: Heavy Metal Exposurementioning
confidence: 99%
“…Animal toxicological models have focused researchers’ attention on specific environmental factors that will be discussed more extensively throughout this review, including fetal exposure to cigarette smoke [12, 13], endocrine disruptors, such as bisphenol A [1416], heavy metals [17, 18], and maternal nutrition including obesity and diabetes [19]. We aim to address the role of these different environmental exposures (Figure 2) on the human fetus or neonate and the subsequent alteration of DNA methylation patterns in varying tissue samples (Summarized in Table 1).…”
Section: Introductionmentioning
confidence: 99%